2016
DOI: 10.1002/jsfa.7624
|View full text |Cite
|
Sign up to set email alerts
|

Long-term toxicity study on genetically modified corn with cry1Ac gene in a Wuzhishan miniature pig model

Abstract: Long-term feeding Bt corn carrying cry1Ac genes to Wuzhishan miniature pigs did not indicate adverse effects on the growth, immune response and health indicators at any stages of growth. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…A long-term (196 days) toxicity study on Bt corn (1.32 mg/kg BW) in a WZSP model found the same results for males. 31 In addition, these differences were not simultaneous in both sexes and were within the normal reference intervals for Wuzhishan pigs. 42 The liver enzyme, AST, was lower in females fed Bt rice than in the control group, paralleling the study of Buzoianu et al 43 ALP values were higher in the Bt group than the Minghui86 group in male pigs but not females.…”
Section: ■ Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…A long-term (196 days) toxicity study on Bt corn (1.32 mg/kg BW) in a WZSP model found the same results for males. 31 In addition, these differences were not simultaneous in both sexes and were within the normal reference intervals for Wuzhishan pigs. 42 The liver enzyme, AST, was lower in females fed Bt rice than in the control group, paralleling the study of Buzoianu et al 43 ALP values were higher in the Bt group than the Minghui86 group in male pigs but not females.…”
Section: ■ Discussionmentioning
confidence: 75%
“…39 Liang Chen et al also reported that hematological parameters did not differ in Wuzhishan miniature pigs that were fed Bt corn expressing the Cry1Ac protein. 31 Sporadic significant differences in serum biochemical values between the Bt and Minghui86 groups were noted. Increased liver size and enzyme levels are indictors of liver dysfunction.…”
Section: ■ Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…So, independent animal testing have recently confirmed the absence of toxicity of MON 810 GM maize in subchronic and chronic toxicity studies (Petrick at al., 2019). During long-term feeding of GM maize to pigs, their live weight, feed conversion and viability were minimally different from the control indicators (Chen et al, 2016). Scholtz et al (2010) found no deterioration of the immune system in quail when fed on genetically modified maize.…”
Section: Introductionmentioning
confidence: 87%
“…Many kinds of research were conducted to evaluate the safety of GM feeding in pigs and rabbits either by giving Bt rice (Liu et al, 2018a, Liu et al, 2018b, Liu et al, 2017 or Bt maize (Chen et al, 2016, Yalçin et al, 2018 presented in Table 2. Chen et al, (2016) conducted a study to investigate the chronic effect of transgenic maize comprise of Cry1Ab protein (1.64 mg/kg) to evaluate the growth performance, immune response and health of Wuzhishan pig after 196-day GM maize feeding. Longterm feeding Bt corn results had no adverse effects of GM maize on pigs.…”
Section: Effects Of Feeding With Gm Crops On Pigs and Rabbitsmentioning
confidence: 99%